Botany - Botany (Canadian Science Publishing, 2026)
Published since 1929, this journal features comprehensive research articles and notes in all segments of plant sciences, including cell and molecular biology, ecology, mycology and plant-microbe interactions, phycology, physiology and biochemistry, structure and development, genetics, genomics, systematics, and phytogeography. It also publishes Methods, Plant Genomic Resources, Discussions (Comments and Replies), and Review articles on topics of current interest, contributed by internationally recognized scientists. Botany also accepts manuscripts written by Indigenous Traditional Knowledge keepers.  Please consult the “Instructions to Authors” for more details.
FI 0.3
Q3
Keywords: Life Sciences; Plant Science; Ciencia de la vida; Botánica; Acuerdos transformativos; Transformative agreements; Biología celular y molecular; Ecología; Micología